Application of a novel exposure limit approach for co-exposure of ‎chemicals: a field study by in-vitro design. - Vahabi Shekarloo, Masoomeh; Panjali, Zahra; Mehrifar, Younes; Ramezanifar, Soleiman; Naziri, Seyed Husein; Ghasemi Koozekonan, Aysa; Moradpour, Zahra; Zendehdel, Rezvan (International Journal of Environmental Health Research, 2023)
This study has suggested an occupational exposure limit (OEL) based on the co-exposure approach in an iron-foundry industry. Respirable dust was collected in an iron casting industry using the NIOSH 0600 method. The DNA damage was obtained by comet assay. The lower confidence interval of the benchmark dose (BMDL) was employed for exposure limit evaluation. The estimated BMDL of the cell line was extrapolated to human subjects. Based on the Hill model, a BMDL 1.65 µg for chemical mixture has been estimated for the A549 cell line. According to uncertainty factors, permitted daily exposure (PDE) was predicted in humans. However, PDE of 3.9 μg/m3 was specified as the time-weighted average limit for toxic respirable dust in the casting industry. In this study, OEL for active respirable dust in the casting industry has been proposed. The industry-based standard for active respirable dust has been proposed for better management of co-exposure.